Integrated hydrogen system analysis across the resource-environment-economy nexus: a case study of China - Maximilian Arras; Anne Yingqiu Liang; Yuning Fu; Zheng Li; Linwei Ma (Journal of Industrial Ecology, 2026)

Thermal Tolerance of Geographical Populations and Their Hybrids in the Ivory Shell Babylonia areolata - Jingqiang Fu; Linwei Nie; Zhenzhen Cai; Weiguang Zou; Yuan Liang; Wengang Lü; Minghui Shen; Xuan Luo; Weiwei You; Tuanyu Guo; Caihuan Ke (Fishes, 2026)
Global warming and summer heatwaves increasingly threaten the survival of cultured Babylonia areolata, but the heat tolerance of different geographical populations and the potential for genetic improvement by hybridization remain poorly understood. In this study, four geographical populations (Thailand, TL; Wanning, WN; Zhao’an, ZA; Changle, CL) and four hybrid combinations (TH, HT, TF, and FT) were compared for mortality rate, median lethal temperature (LT50), and critical thermal maximum (CTMax) under controlled thermal stress. The results showed that the low-latitude TL population exhibited significantly higher LT50 (36.49 ± 0.05 °C) and CTMax (35.77 ± 0.52 °C) than the high-latitude CL and ZA populations (LT50: 35.90 ± 0.05–36.02 ± 0.04 °C; CTMax: 35.12 ± 0.77–35.26 ± 0.53 °C). All four hybrids had improved heat tolerance compared with their low parents, with TH and HT showing the strongest mid-parent heterosis (e.g., 73.68–78.94% for survival at 36.5 °C). However, none significantly exceeded the high-parent performance (TL), indicating only mid-parent heterosis. These findings reveal significant genetic variation in heat tolerance among geographical populations of B. areolata and confirm that cross-breeding can effectively enhance heat tolerance, though it does not produce transgressive superiority. This study provides key genetic resources and a theoretical basis for breeding heat-tolerant strains of B. areolata.

SAF-YOLO: Super-resolution augmented detection model with visual state space enhancement for safflower filament picking - Duan Mengyu; Wang Xiaorong; Qiu Linwei; Li Menghao; Chen Jinrong; He Liang (Precision Agriculture, 2026)

Preparation of high-specificity monoclonal antibody based on rational hapten design and development of immunoassay for accurate detection of dexamethasone in milk and animal tissues - Hongfei Yang; Liangni Qin; Jiaxu Xiao; Xiaoming Pan; Shiyun Han; Linwei Zhang; Jixiang Liang; Yu Si; Hao Wen; Long Li; Xingyu Wang; Xiaojuan Zhang; et al. (Food Bioscience, 2025)

Biodegradable polylactic acid (PLA) copolymer materials: Structural design, synthesis strategy, the relationship between structure and performance, industrial application - Rongrong Ji; Fan Mo; Linwei Liang; Chen Tian; Shixing Dong; Chang Deng; Hao Wu; Ling Zhou; Xipo Zhao (Chemical Engineering Journal, 2025)

Localized surface plasmon enhancement strategy with synergistic dual-mechanism fluorescence quenching for developing highly sensitive lateral flow immunoassays - Mingyue Ding; Hao Wen; Long Li; Yu Si; Jixiang Liang; Shixiang Wu; Linwei Zhang; Hongfei Yang; Shiyun Han; Xiaoming Pan; Yiting Wang; Jiacan Wang; et al. (Chemical Engineering Journal, 2025)

Computer-aided precise hapten design strategy for the monospecific detection of altrenogest: Experimental validation and analysis of the molecular recognition mechanism - Hongfei Yang; Hao Wen; Yu Si; Mingyue Ding; Yiting Liu; Ziyan Yu; Linwei Zhang; Jiacan Wang; Xiaoming Pan; Shiyun Han; Yiting Wang; Shixiang Wu; et al. (Food Chemistry, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

7-Hydroxylathyrol defeats geminivirus through targeting C4 and activating host defense - Bi Wang; Xiaoxiao Xu; Wenhao Liang; Tong Shi; Qizhi Wang; Yu Chen; Sha Chen; Fei Liu; Linwei Li (Pesticide Biochemistry and Physiology, 2025)

Preparation of high-affinity and high-specificity monoclonal antibody and development of ultra-sensitive immunoassay for the detection of 1-aminohydantoin, the metabolite of nitrofurantoin - Hongfei Yang; Liangni Qin; Hao Wen; Mingyue Ding; Linwei Zhang; Jiaxu Xiao; Jixiang Liang; Yiting Liu; Ziyan Yu; Dapeng Peng (Food Chemistry, 2024)

Dietary zinc levels affect growth, appetite, and lipid metabolism of Chinese perch (Siniperca chuatsi) - Di Peng; Linwei Yang; Xu-Fang Liang; Farui Chai (Fish Physiology and Biochemistry, 2023)

The spatial scale dependence of diazotrophic and bacterial community assembly in paddy soil - Qun Gao; Yunfeng Yang; Jiajie Feng; Renmao Tian; Xue Guo; Daliang Ning; Lauren Hale; Mengmeng Wang; Jingmin Cheng; Linwei Wu; Mengxin Zhao; Jianshu Zhao; et al. (Global Ecology and Biogeography, 2019)
Aim The factors driving microbial community β‐diversity (variation in composition) at different spatial scales yield fundamental insights into the mechanisms that maintain ecosystem biodiversity, which as yet are uncertain. Here, we explore whether spatial scale‐dependent patterns of β‐diversity vary between microbial functional groups and bacterial taxa (i.e., diazotrophic and bacterial communities) across local to regional scales (from metres to hundreds of kilometres). Location Eastern China. Time period October and November 2015. Major taxa studied Diazotrophic and bacterial communities. Methods We use two complementary statistical tools to unveil biotic mechanisms (i.e., species association) underlying variation in β‐diversity of diazotrophic and bacterial communities. We examined distance–decay slopes of both communities at the local (1–113 m), meso‐ (3.4–39 km) and regional (103–668 km) scales. We used an environmentally constrained checkerboard score and topological features of association networks as indices of species association. We then calculated contributions of species association, abiotic factors and geographical distance to explain community β‐diversity. The scale‐dependent distance–decay relationships were also examined in ubiquitous (high occupancy across samples) and endemic communities of diazotrophs and bacteria. Results Diazotrophs displayed steeper distance–decay slopes than bacteria, suggesting that the β‐diversity of diazotrophic communities was more variable. The distance–decay slopes were dependent on spatial scales in both communities, owing to different contributions of geographical distance, abiotic factors and species association at three spatial scales. Intriguingly, species association was greater and contributed more to community β‐diversity than other forces at the local scale, implying that species association could greatly alter community structures. Main conclusions Drivers of diazotrophic and bacterial community β‐diversity depended on spatial scales, resulting in different distance–decay patterns. Moreover, this was the first study to use two methods to demonstrate that species association played important, but as yet unrecognized, roles in driving spatial scale‐dependent β‐diversity.

Dissimilar responses of fungal and bacterial communities to soil transplantation simulating abrupt climate changes - Mengxin Zhao; Bo Sun; Linwei Wu; Feng Wang; Chongqing Wen; Mengmeng Wang; Yuting Liang; Lauren Hale; Jizhong Zhou; Yunfeng Yang (Molecular Ecology, 2019)
Both fungi and bacteria play essential roles in regulating soil carbon cycling. To predict future carbon stability, it is imperative to understand their responses to environmental changes, which is subject to large uncertainty. As current global warming is causing range shifts toward higher latitudes, we conducted three reciprocal soil transplantation experiments over large transects in 2005 to simulate abrupt climate changes. Six years after soil transplantation, fungal biomass of transplanted soils showed a general pattern of changes from donor sites to destination, which were more obvious in bare fallow soils than in maize cropped soils. Strikingly, fungal community compositions were clustered by sites, demonstrating that fungi of transplanted soils acclimatized to the destination environment. Several fungal taxa displayed sharp changes in relative abundance, including Podospora , Chaetomium , Mortierella and Phialemonium . In contrast, bacterial communities remained largely unchanged. Consistent with the important role of fungi in affecting soil carbon cycling, 8.1%–10.0% of fungal genes encoding carbon‐decomposing enzymes were significantly ( p